2010
DOI: 10.1186/1471-2377-10-22
|View full text |Cite
|
Sign up to set email alerts
|

Anemia status, hemoglobin concentration and outcome after acute stroke: a cohort study

Abstract: BackgroundIn the setting of an acute stroke, anemia has the potential to worsen brain ischemia, however, the relationship between the entire range of hemoglobin to long-term outcome is not well understood.MethodsWe examined the association between World Health Organization-defined admission anemia status (hemoglobin<13 in males, <12 g/dl in women) and hemoglobin concentration and 1-year outcome among 859 consecutive patients with acute stroke (ischemic or intracerebral hemorrhage).ResultsThe mean baseline hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
96
4
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 30 publications
4
96
4
2
Order By: Relevance
“…After detailed screening, 20 studies were included in our systematic review; the flow chart of study selection is shown in Figure 4, and Tables 5 and 6 show the key features of the selected studies. Overall, 10 studies assessed the impact of anemia on stroke1, 2, 10, 16, 17, 18, 19, 20, 21, 22 and 10 evaluated the association between stroke and hemoglobin levels 6, 7, 8, 9, 23, 24, 25, 26, 27, 28. In terms of study design, 3 were retrospective cohort studies,1, 16, 20 13 were prospective cohort studies,2, 6, 7, 8, 9, 10, 17, 18, 19, 22, 23, 24, 25 and 2 were secondary analyses of randomized control trials 27, 28.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After detailed screening, 20 studies were included in our systematic review; the flow chart of study selection is shown in Figure 4, and Tables 5 and 6 show the key features of the selected studies. Overall, 10 studies assessed the impact of anemia on stroke1, 2, 10, 16, 17, 18, 19, 20, 21, 22 and 10 evaluated the association between stroke and hemoglobin levels 6, 7, 8, 9, 23, 24, 25, 26, 27, 28. In terms of study design, 3 were retrospective cohort studies,1, 16, 20 13 were prospective cohort studies,2, 6, 7, 8, 9, 10, 17, 18, 19, 22, 23, 24, 25 and 2 were secondary analyses of randomized control trials 27, 28.…”
Section: Resultsmentioning
confidence: 99%
“…There were also 2 studies that did not state the design 21, 26. There was a high degree of diversity in geographic location, with cohorts from Germany,8, 19, 25 Switzerland,16, 20 the United States,18, 24 the People's Republic of China,2, 22 Canada,23, 28 India,6 Israel,10 the Republic of Korea,9 Denmark,21 Taiwan,17 the United Kingdom,26 and Poland 7. In addition, 2 studies were conducted across multiple countries 1, 27.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations